If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2(-2x + 5) = 2 Reorder the terms: x + -2(5 + -2x) = 2 x + (5 * -2 + -2x * -2) = 2 x + (-10 + 4x) = 2 Reorder the terms: -10 + x + 4x = 2 Combine like terms: x + 4x = 5x -10 + 5x = 2 Solving -10 + 5x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 2 + 10 5x = 2 + 10 Combine like terms: 2 + 10 = 12 5x = 12 Divide each side by '5'. x = 2.4 Simplifying x = 2.4
| 12x+22=-9x-41 | | -144=-8x | | 3n-8=32n | | x=ky+f | | 6x-99=-5x | | 4(x-1)+3(x+1)= | | 217.25=3 | | 4x-(2x+5)=3x-10 | | 6m-6=6m+18 | | 2x+3x+3=-12 | | 21p-62=38+p | | 8x+12-2x-5=3 | | y=kx+f | | 2(2+5x)=9(x-1) | | 81c^2+18c+1= | | 9[5-7(x-1)]+6[(5x+7)-8]=11x-336 | | (1-5j)+(-2-6j)=-1-11j | | 6x+x^2=84 | | 9c^2-8c-1= | | 4-x=4x+19 | | -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= | | 15z+30=15y+30 | | 6(W+3)=-2(5W-5)+2W |